2020
DOI: 10.1038/s41419-020-2335-1
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing STAT5 signaling affects osteosarcoma growth and stemness

Abstract: Osteosarcoma (OS) is the most common primary bone tumor that primarily affects children and adolescents. Studies suggested that dysregulation JAK/STAT signaling promotes the development of OS. Cells treated with pimozide, a STAT5 inhibitor suppressed proliferation and colony formation and induced sub G0/G1 cell cycle arrest and apoptosis. There was a reduction in cyclin D1 and CDK2 expression and Rb phosphorylation, and activation of Caspase-3 and PARP cleavage. In addition, pimozide suppressed the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 51 publications
0
59
0
Order By: Relevance
“…The Wnt/b-catenin signaling pathway has been reported to be involved in controlling OS development. 21 Because FZD3 is a direct target of miR-182-5p, we investigated whether miR-182-5p affected Wnt by regulating FDZ3. Overexpression of miR-182-5p significantly decreased b-catenin nuclear accumulation, whereas b-catenin was increased in the cytoplasm (Figures S3A and S3B).…”
Section: Snhg10 Activates the Wnt/b-catenin Pathway To Promote Os Progressionmentioning
confidence: 99%
“…The Wnt/b-catenin signaling pathway has been reported to be involved in controlling OS development. 21 Because FZD3 is a direct target of miR-182-5p, we investigated whether miR-182-5p affected Wnt by regulating FDZ3. Overexpression of miR-182-5p significantly decreased b-catenin nuclear accumulation, whereas b-catenin was increased in the cytoplasm (Figures S3A and S3B).…”
Section: Snhg10 Activates the Wnt/b-catenin Pathway To Promote Os Progressionmentioning
confidence: 99%
“…Bromocriptine regulates several signaling pathways in tumorigenesis and progression, including the PI3K/AKT and the MAPK/JNK/ERK signaling pathways (4,40). Previous studies have also revealed that STAT proteins are important downstream targets of MAPK and JAK signaling (19,(41)(42)(43). Although the exact mechanism is not completely understood, it has been hypothesized that there may be crosstalk between the STAT5 and JNK/MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to evaluate the activation status of the JAK2/STAT5 signaling pathway in bromocriptine-resistant prolactinoma tissues and to assess the potential chemotherapeutic sensitizing effect of pimozide on the bromocriptine-resistant prolactinoma cells. As tumor stem cells serve a vital role in tumor recurrence, metastasis and drug resistance ( 16 , 18 , 19 ), the effect of pimozide on prolactinoma cell stemness was also assessed. Collectively, these experiments provide a rationale for further clinical studies on the use of pimozide as a chemosensitizer in bromocriptine-resistant prolactinomas.…”
Section: Introductionmentioning
confidence: 99%
“…However, more and more studies have indicated that it also held the ability to suppress cancer cells [73][74][75]. Furthermore, pimozide has been demonstrated that its treatment resulted in the decreased level of BCL2 [76]. In addition to the treatment of chronic immune thrombocytopenia [77], there is a study showing that repurposing of fostamatinib is an effective treatment to inhibit metastatic tumor outgrowth in breast cancer [78].…”
Section: The Identified Biomarkers and Their Corresponding Potential Multiple-molecule Drug To Prevent The Progression From Early To Middmentioning
confidence: 99%